Street children in Sierra Leone who forgive those who physically and sexually abuse them: a quantitative and qualitative analysis - Hinton, Samuel (Edwin Mellen Press, 2009)
Making connections -- Problem and setting -- Theology, theory, and poverty -- Working with street children -- Failed peace and retrospective prayer -- Methodology -- Questionnaire -- Survey response analysis -- Millenium development goals and education -- International dimensions -- Summary and conclusions